Ankylosing spondylitis patients commencing biologic therapy have high baseline levels of comorbidity: A report from the Australian Rheumatology Association database - Oldroyd, J.; Schachna, L.; Buchbinder, R.; Staples, M.; Murphy, B.; Bond, M.; Briggs, Andrew; Lassere, M.; March, L. (Hindawi Publishing Company, 2009)
Aims. To compare the baseline characteristics of a population-based cohort of patients with ankylosing spondylitis (AS) commencing biological therapy to the reported characteristics of bDMARD randomised controlled trials (RCTs) participants. Methods. Descriptive analysis of AS participants in the Australian Rheumatology Association Database (ARAD) who were commencing bDMARD therapy. Results. Up to December 2008, 389 patients with AS were enrolled in ARAD. 354 (91.0%) had taken bDMARDs at some time, and 198 (55.9%) completed their entry questionnaire prior to or within 6 months of commencing bDMARDs. 131 (66.1%) had at least one comorbid condition, and 24 (6.8%) had a previous malignancy (15 nonmelanoma skin, 4 melanoma, 2 prostate, 1 breast, cervix, and bowel). Compared with RCT participants, ARAD participants were older, had longer disease duration and higher baseline disease activity. Conclusions. AS patients commencing bDMARDs in routine care are significantly different to RCT participants and have significant baseline comorbidities.